Modulatory Effect of Eui-E-In-Tang on Serum Leptin Concentration in Obese Korean Female Adults: A Randomized Controlled Trial. (18th August 2016) - Song, Yun-Kyung; Lee, Ji-Young; Park, Wansu
Abstract : Background. Obesity is associated with chronic inflammation and cytokines. However, to date, the relationship between the serum levels of cytokines in obese individuals and taking herbal drugs remains largely unexplored. Methods. Serum cytokines were assessed by multiplex cytokine profiling assay. Serum samples of obese female Korean adults (obese group;n = 20 ) as well as normal female Korean adults (normal group;n = 21 ) were collected at the start and end of study period. Twenty obese female Korean adults were randomized to receive Eui-E-In-Tang (Eui-E-In-Tang group;n = 9 ) at a daily dose of 9 g or a matched placebo (placebo group;n = 11 ) for 12 weeks. Results. According to investigating serum cytokine levels at the start point of this study, the serum C-peptide, insulin, leptin, lipocalin-2, and adipsin levels in the obese group were found to be significantly higher than in the normal group. And the investigation of serum cytokine levels at the end point of this study demonstrated that mean serum leptin of Eui-E-In-Tang group was found to be significantly reduced (P = 0.037 ). Conclusions. This study provides preliminary evidence that Eui-E-In-Tang may exert immunomodulatory effect via altering the circulating concentration of leptin in Korean female adults.